Teks Boys Love Sebagai Media Negosiasi Gender dan Seksualitas Penggemar wanita - Ade Fristy Syahara (Mahesa Research Center, 2023)
This article examines the process of female Kpop fans' acceptance of boys' love texts and fans' negotiations against gays in cyberspace and the real world through the boys' love texts they read. Boys love a subgenre of fanfiction that focuses on romantic relationships between men using Kpop idols as visualizations. The data were obtained using a cyber ethnography approach and analyzed using Spradley's taxonomy and Tania Zittoun's internalization theory. I think that interest in Kpop can be a medium for interest in and acceptance of boys' love texts, forming a virtual space that serves to consume, produce and discuss boys' love texts which affect the acceptance of gays, which is diverse and different for each individual. Acceptance of boys' love texts in cyberspace is not always directly proportional to gay approval in the real world. There is a paradox in gay favor in virtual and real worlds caused by differences in reader backgrounds, binding values , and norms, individual understanding of differences in sexual orientation, and direct contact with gay individuals.